Foxp3+ Helios+ regulatory T cells are expanded in active systemic lupus erythematosus. Issue 9 (21st December 2012) - Alexander, Tobias; Sattler, Arne; Templin, Lars; Kohler, Siegfried; Groß, Christian; Meisel, Andreas; Sawitzki, Birgit; Burmester, Gerd-Rüdiger; Arnold, Renate; Radbruch, Andreas; Thiel, Andreas; Hiepe, Falk
Abstract : Objectives: Recent data debate the suitability of Helios, an Ikaros family member, as a marker for thymic-derived regulatory T cells (Treg). Nevertheless, Foxp3 + Helios + Treg may be of particular relevance in mediating immune tolerance in chronic autoimmunity, such as systemic lupus erythematosus (SLE), as they possess enhanced suppressive function, compared to Foxp3 + Helios − Treg. Methods: Multicolour flow cytometry was performed to analyse Foxp3 and Helios expression in peripheral blood CD4 T cells from SLE patients, compared to healthy controls (HC) and systemic sclerosis (SSc) and rheumatoid arthritis (RA) patients. Cytokine production, chemokine receptor expression for CXCR3 and CCR4, basal signal transducer and activator of transcription 5 (STAT5)a phosphorylation levels and T-cell receptor (TCR) Vβ repertoire were analysed by flow cytometry, and the methylation status of the Foxp3 locus (Treg-specific demethylated region, TSDR) by real-time PCR. Results: Frequencies of Foxp3 + Helios + Treg, unlike Foxp3 + Helios − T cells, were significantly increased in SLE patients and positively correlated with disease activity, whereas they were unaltered in SSc and RA patients. Compared to HC, Foxp3 + Helios + Treg in SLE predominantly displayed a CD45RA − /CD31 − /FoxP3 low memory phenotype with increased Ki-67 expression, enhanced basal pSTAT5a levels and a restricted TCR repertoire. Nonetheless, similar to HC, Foxp3 + Helios + Treg in SLE lacked effector cytokine production, possessed a highly demethylated TSDR and expressed comparable levels of CXCR3 and CCR4. Conclusions: Our data suggest that Helios-expressing Foxp3 + Treg with functional suppressive capacity and migratory potential into inflamed tissues are expanded in active SLE, presumably through γ-chain signalling cytokines and TCR stimulation, to compensate for autoreactive effector responses.